2020
DOI: 10.2147/ott.s262359
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dihydrotestosterone Induces Proliferation, Migration, and Invasion of Human Glioblastoma Cell Lines</p>

Abstract: Introduction Glioblastomas (GBM) are the most frequent and aggressive human brain tumors due to their high capacity to migrate, invade healthy brain tissue, and resist anticancer therapies. It has been reported that testosterone (T) levels are higher in patients with GBM than in healthy controls. It has also been dem{}onstrated that T induces proliferation, migration, and invasion of human GBM cell lines. T is mainly metabolized to 5α-dihydrotestosterone (DHT) by the enzyme 5α-reductase (5αR), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
(43 reference statements)
2
14
0
Order By: Relevance
“…recently showed that DHT had an independent and stronger effect than testosterone toward enhancing cell growth, proliferation, migration, and invasion in U87 and U251 cells in vitro . [ 30 ] These results were also confirmed by Orozco et al . wherein it was shown that DHT (not androstenedione) could independently increase cell viability, proliferation, and invasion in human U87 GBM cells in vitro in a more potent fashion than testosterone.…”
Section: Role Of Androgens In Gliomasupporting
confidence: 79%
See 2 more Smart Citations
“…recently showed that DHT had an independent and stronger effect than testosterone toward enhancing cell growth, proliferation, migration, and invasion in U87 and U251 cells in vitro . [ 30 ] These results were also confirmed by Orozco et al . wherein it was shown that DHT (not androstenedione) could independently increase cell viability, proliferation, and invasion in human U87 GBM cells in vitro in a more potent fashion than testosterone.…”
Section: Role Of Androgens In Gliomasupporting
confidence: 79%
“…Apart from this, AR expression has been confirmed in various glioma cell lines (A172, LN18, LN229, M059, T98G, U87, U118MG, U138MG, and U251MG). [ 22 25 26 27 28 29 30 ]…”
Section: Role Of Androgens In Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Bunevicius and colleagues [84] suggested a greater prenatal testosterone and lower prenatal estrogen exposure in brain tumor patients [84,85]. Moreover, testosterone (100 nM) and DHT (10 nM) exposed U87, U251 and D54 GBM cells displayed enhanced proliferation, migration and invasion [86,87]. In rats xenografted with GBM, experimental castration reduced the incidence of tumor development and increased the time between implantation and death [88].…”
Section: Exogenous Androgen Exposure: High Levels and Increased Maligmentioning
confidence: 99%
“…In this study, the TCGA Data Analysis of mRNA expression of AR, 5αR1, and 5αR2 from 196 grade II, 223 grade III, and 139 grades IV were compared with 249 healthy brain cortex samples. This analysis showed that AR and 5αR2 expression was higher in all astrocytomas than the healthy brain; however, no statistically significant differences were observed between astrocytoma grades [ 110 ]. Werner and cols determined that AR expression at the transcript and protein levels in LN18, T98G glioblastoma cell lines, patient-derived xenografts (PDX), and human tumors overlapped with the expression of this receptor in primary prostate cancer.…”
Section: Glioblastomamentioning
confidence: 99%